Seguir un delito a lo largo del tiempo: interrogaciones al cuerpo documental de pleitos judiciales por injuria en Chile, siglos XVIII y XIX - Albornoz Vásquez, María Eugenia (Revista de Historia Social y de las Mentalidades, 2011)
This article is a methodological reflection which i s raised from the dialog with the documentary body of lawsuits built with the purpose of study the slander and/or libel (injures) situations in Chile between 1700 and 1784 . Without avoiding the theoretical elements of the problem under investigation, the di scussion is centered in aspects belonging to the work of historiography, which becomes shaken by the analysis of a great amount of documents similar in principle but heterogeneous an d dissimilar in reality. The result is theenrichment of both the questions and the analysis i tself, derived from a stage which seldom is thought thoroughly and much less is shared, but is inherent to the process of making history and, if it is tackled honestly, it may not only modify the status of the documents and social roles of the institutions that generate them but, above all, it might modify the understanding of individuals and societies in the past.